The Role of Local Communities in Supporting Children After Divorce in Aceh - Rahim, Zhila; Maulida Shanti Yusuf; Khairun Nisa; Lalila Alvina Syahrani (Inovan Publisher, 2025)
Divorce is an increasingly complex social problem in Indonesia, including in Aceh. It has a significant impact on children, emotionally, socially and psychologically. This research aims to examine the role of local communities, particularly customary institutions, in providing support to children after divorce in Aceh. This research uses a qualitative approach with literature study as the main method. Data were obtained from journal articles, theses, and related literature relevant to the research topic. Data analysis was conducted systematically through data collection, data reduction, data presentation, and data verification. The results showed that local communities, especially customary institutions, have great potential in providing support to post-divorce children through various forms, such as emotional, social, and practical support.